Study the Chemical Compassion of Gallstone and its Relationship to Acute Cholecystitis - Ameerah M. Zarzoor (Journal of Global Pharma Technology, 2016)
All over the world cholelithiasis is a main reason of morbidity. Gallstones are public between the general people; many people are ignorant of their presence because they not commonly cause symptoms. The detached of this revision was to conclude the chemical conformation of gallstones and any relationship between the composition of the stone and initiation of acute cholecystitis. For 50 patients (13 males and 37 females), the chemical composition of gallstones was tested. (46 %) of the sample are in age groups (40-50) years old. A seventy four of study participants were female. In 50 gallstone, cholesterol stones 27 (54 %), mixed stone 20 (40 %)   and pigment stones was 3 (6 %). The modifier of female:  male was (5.3:1). The  studying  shown  that Cholelithiasis occurrence  in  the age  group 40-50   ( 23 cases)   is  maximum  follow them   13, 9 and 5 cases for  age  groups  30-39,  51-61  and  62 years  old and  more respectively. About 62% of patients  with  cholelithiasis have  acute  cholecystitis Conclusion: In Al-Kut city  cholesterol gall stones  is  great   incidence   as  associated  to mixed  & pigmented  gall stones and  most patients with cholelithiasis have  acute cholecystitisKeywords: Gall stone, Cholelithiasis, Cholesterol, Bilirubin, Calcium.